Development and Operation of a Video Teleconsultation System Using Integrated Medical Equipment Gateway: a National Project for Workers in Underserved Areas. - Park, Hyun Sang; Kim, Kwang il; Soh, Jae Young; Hyun, Young Ho; Lee, Bang Eun; Lee, Jong Hwa; Jo, Jung Gwon; Lee, Han Chae; Kim, Hwa Sun (Journal of Medical Systems, 2020)
Worker health centers and health zones provide occupational healthcare services to workers in underserved areas of industrial health. Health zones cannot counsel workers on occupational disease prevention; worker health center personnel have to provide such services through in-person visits. Video teleconsultation can increase the accessibility of high-quality services to workers who visit health zones and improve professional personnel's efficiency. This study aimed to develop a system and an infrastructure that could facilitate video teleconsultation services between worker health centers and health zones, and analyze the services' operation status. A video teleconsultation process based on the role of local and remote institutions was designed. Based on the designed services, a web system supporting teleconsultation and an integrated gateway guaranteeing the interface with medical equipment in the web environment was developed. After analyzing the working environment, an infrastructure consisting of networks, video equipment, medical equipment, and servers necessary for teleconsultation was designed. Statistical results from the developed system and a satisfaction survey conducted by the Korea Occupational Safety and Health Agency were used to analyze the video teleconsultation services' operation status. A system, gateway, and hardware infrastructure within 21 worker health centers and 21 health zones has been operating this service since January 1, 2018. Over two years, the total number of teleconsultation service users was 4979, and the total number of questionnaire respondents was 1270. The total number of service activities was 6388 and total satisfaction was rated as 4.58 (± 0.59) out of 5. In this study, video teleconsultation services were evaluated as being very satisfactory. In particular, service accessibility and local medical personnel service were rated highly, demonstrating that the developed system and infrastructure were well designed according to the goals of the project.